THE INFLUENCE OF MARKETING COMMUNICATIONS AND PROMOTION OF SALES TARGETS PT. SUMINSURYA MESINDOLESTARI - Venesa; Syawaluddin Syawaluddin; Mila Asmawiani; Thomas Sumarsan Goh (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
This research was conducted on consumers who work at PT. Suminsurya Mesindolestari. The purpose of this study was to determine and analyze the effect of marketing communications and promotions on sales targets. The population and sample in this study amounted to 57 people. The sampling technique used is saturated. Data collection techniques are by distributing questionnaires and interviews. Data analysis used multiple linear regression analysis. The conclusion in the study that simultaneously marketing and promotion communications have a positive and significant effect on the sales target of PT. Suminsurya Mesindolestari. Partially, marketing communication has no effect on the sales target of PT. Suminsurya Mesindolestari. Partially, promotion has a positive and significant effect on the achievement of the sales target of PT. Suminsurya Mesindolestari. The magnitude of the coefficient of determination can be seen from the Adjusted R Square value is: 0.459 means that Marketing and Promotion Communications is able to explain the Sales Target of 45.9% while the remaining 54.1% is influenced by variables not examined such as: prices, discounts, promotions, and so on.